2008
DOI: 10.1080/00016340701802888
|View full text |Cite
|
Sign up to set email alerts
|

Group B streptococcal carriage in Sweden: a national study on risk factors for mother and infant colonisation

Abstract: Maternal GBS prevalence and infant transfer rate were high in Sweden. Males were more frequently colonised than females. The sensitivity of maternal cultures decreased with the duration of sample transport. Clindamycin resistance was scarce. The use of intrapartum antibiotics was limited in parturients with obstetric risk factors for early onset group B streptococcal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
45
3
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 39 publications
(44 reference statements)
15
45
3
5
Order By: Relevance
“…Some individual European nations have adopted a modified approach of this strategy by excluding preterm labor or ruptured membranes from these specific risk factors [29]. The use of risk-based policy in these nations reflect the belief that their low national incidence of GBS EOD will likely not decrease further with the introduction of universal culture-based screening, and solely increase maternal-fetal exposure to the adverse effects of antibiotics, mainly antimicrobial resistance and potential anaphylactic reactions [30,31]. For these countries, the implementation of universal GBS screening may lead as well to further medicalization of labor and require more counseling and a higher level of care for many more women, increasing costs and increasing the risk of obstetrical interventions [29,32].…”
Section: Current Prevention Strategies Used In European Countries Andmentioning
confidence: 99%
“…Some individual European nations have adopted a modified approach of this strategy by excluding preterm labor or ruptured membranes from these specific risk factors [29]. The use of risk-based policy in these nations reflect the belief that their low national incidence of GBS EOD will likely not decrease further with the introduction of universal culture-based screening, and solely increase maternal-fetal exposure to the adverse effects of antibiotics, mainly antimicrobial resistance and potential anaphylactic reactions [30,31]. For these countries, the implementation of universal GBS screening may lead as well to further medicalization of labor and require more counseling and a higher level of care for many more women, increasing costs and increasing the risk of obstetrical interventions [29,32].…”
Section: Current Prevention Strategies Used In European Countries Andmentioning
confidence: 99%
“…During 2005 a Swedish, population-based study of GBS carriage in parturients and infants, and risk factors for colonization, was performed before a regular national IAP program had been implemented (15). Of 1,569 mother/infant pairs examined the vaginal/rectal carriage rate of the mothers was 25,4%.…”
Section: Introductionmentioning
confidence: 99%
“…22 Similar to our findings, previous studies have shown no association with diabetes 19,22 or alcohol use 19,22 and minimal to no relationship with parity. 18,19,22 Unlike our study (which used type of insurance as a proxy), authors from Washington state found an association between maternal GBS colonization and both educational level and income. 22 We found no association with tobacco use and maternal age; however, these associations were inconsistently found in other studies.…”
Section: Discussionmentioning
confidence: 45%
“…A Swedish study revealed no significant differences in colonization rates between regions of the country or with respect to the population size of the municipality. 18 Geographic differences noted in our study were independent of other demographic variables such as age, race/ethnicity and insurance status. The increased colonization rate in one suburban village in eastern Wisconsin (34.3%) was surprising and without explanation.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation